A putative 6‐transmembrane nitrate transporter OsNRT1.1b plays a key role in rice under low nitrogen. Issue 6 (18th September 2015) - Fan, Xiaorong; Feng, Huimin; Tan, Yawen; Xu, Yanling; Miao, Qisong; Xu, Guohua
Abstract: OsNRT1.1a is a low‐affinity nitrate (NO3 − ) transporter gene. In this study, another mRNA splicing product, OsNRT1.1b, putatively encoding a protein with six transmembrane domains, was identified based on the rice genomic database and bioinformatics analysis. OsNRT1.1a/OsNRT1.1b expression in Xenopus oocytes showed OsNRT1.1a ‐expressing oocytes accumulated 15 N levels to about half as compared to OsNRT1 .1b‐expressing oocytes. The electrophysiological recording of OsNRT1.1b ‐expressing oocytes treated with 0.25 mM NO3 − confirmed 15 N accumulation data. More functional assays were performed to examine the function of OsNRT1.1b in rice. The expression of both OsNRT1.1a and OsNRT1.1b was abundant in roots and downregulated by nitrogen (N) deficiency. The shoot biomass of transgenic rice plants with OsNRT1.1a or OsNRT1.1b overexpression increased under various N supplies under hydroponic conditions compared to wild‐type (WT). The OsNRT1.1a overexpression lines showed increased plant N accumulation compared to the WT in 1.25 mM NH4 NO3 and 2.5 mM NO3 – or NH4 + treatments, but not in 0.125 mM NH4 NO3 . However, OsNRT1.1b overexpression lines increased total N accumulation in all N treatments, including 0.125 mM NH4 NO3, suggesting that under low N condition, OsNRT1.1b would accumulate more N in plants and improve rice growth, but also that OsNRT1.1a had no such function in rice plants. Abstract : A full𣀐size nitrate transporter usually has 12 transmembrane helixes. In here, we presented that a half‐size nitrate transporter, one splicing product of OsNRT1.1 gene, can also function well in nitrate transport and even behave better than its full size product under nitrogen deficiency in rice.